Analisis Penentuan Strategi Pemasaran Optimal Warung Jajanan Mamadamay Cintaraja Tasikmalaya Menggunakan Metode Game Theory - Aripin, Wahyu Teri; Fuadi, Mamik M.; Bilqis, Mina Rahmani (LPPM Sekolah Tinggi Teknologi Cipasung, 2024)
Warung Jajanan Mamadamay is one of the UMKM located in the Cintaraja area of Tasikmalaya which is engaged in culinary or fast food. Warung Jajanan Mamadamay has two marketing strategies, namely offline marketing and online marketing. The emergence of competitors in the Cintaraja area and the need for Mamadamay Snack Stalls to improve and maintain their businesses so that they can survive requires an optimal method/strategy. Game theory is a theory to complete and provide an overview to both parties in making decisions when determining the strategy to be applied. The optimal strategy at Warung Jajanan Mamadamay with Game Theory uses the Marketing Mix 4 P variables, namely Product, Price, Place and Promotion. Based on data processing with Game Theory and data analysis, the optimal marketing strategy at Warung Jajanan Mamadamay at this time is: offline marketing using the product variable strategy and online marketing using the promotion variable strategy.